Associations between handedness and cerebral lateralisation for language: a comparison of three measures in children. - Margriet A Groen; Andrew J O Whitehouse; Nicholas A Badcock; Dorothy V M Bishop (PLoS ONE)
It has been known for many years that hand preference is associated with cerebral lateralisation for language, but the relationship is weak and indirect. It has been suggested that quantitative measures of differential hand skill or reaching preference may provide more valid measures than traditional inventories, but to date these have not been validated against direct measures of cerebral lateralisation. We investigated the associations of three different handedness assessments; 1) a hand preference inventory, 2) a measure of relative hand skill, and 3) performance on a reaching task; with cerebral lateralisation for language function as derived from functional transcranial Doppler ultrasound during a language production task, in a group of 57 typically developing children aged from 6 to 16 years. Significant correlations between cerebral lateralisation for language production and handedness were found for a short version of the inventory and for performance on the reaching task. However, confidence intervals for the correlations overlapped and no one measure emerged as clearly superior to the others. The best handedness measures accounted for only 8-16% of the variance in cerebral lateralisation. These findings indicate that researchers should not rely on handedness as an indicator of cerebral lateralisation for language. They also imply that lateralisation of language and motor functions in the human brain show considerable independence from one another.